KEPELOPORAN MAHMŪD TAYMŪR DALAM CERPEN ARAB MODERN - Tatik Maryatut Tasnimah (Sunan Kalijaga State Islamic University Yogyakarta, 2008)
Mahmud Taymur was one of the founders of the Egyptian realistic short story, also known as Syaikh al-Qisasah alQashīrah. Remaining productive over a long life Taymur wrote extensive literary criticism and was the author of short stories, novellas, and plays totaling a score of volumes. Most notable for his skill in characterization, he achieved a literary eminence shared by few other Arabs of his generation in Cairo in 1947, and individual stories by him gave and appeared widely in English and European Anthologies. Taymur’s early works were influenced by Chekhov and Maupassant. His short stories of the 1920s and 1930s portrayed various social strata in Egypt. Taymur’s prose is marked by humanism and psychological subtlety. In the late 1930s and in the 1940s his prose was influenced by symbolism but after the revolutionary coup of 1952, Taymur’s works were predominantly realistic.